A systematic review of flexible work arrangements in china: development trends and socioeconomic impacts over the last decade - Zhang, Sisi; Chan, Siaw Leng; Abang Abai, Dayang Shobihah (Human Resources Management Academic Research Society (HRMARS), 2024)
Flexible Work Arrangements (FWAs) have increasingly become a key feature of modern work systems, driven by the rapid progression of globalization and information technology. This systematic review synthesizes findings from 25 peer-reviewed articles published between 2014 and 2024 to examine the development, drivers, and impacts of FWAs in China. The review reveals a widespread adoption of FWAs in various forms, such as flexible core hours and telecommuting. Policy changes, particularly adjustments in maternity leave regulations, have played a crucial role in facilitating this shift. The primary drivers behind adopting FWAs include technological advancements, the diversification of workforce needs, and shifts in organizational strategies. Implementing FWAs is associated with positive outcomes, including enhanced job satisfaction, task performance, creativity, work-family balance, and reduced turnover intentions. This review also identifies cultural nuances in adopting FWAs and offers strategic insights for optimizing their application in China.